How Did Prospective Elementary School Teacher Learn Citizenship Education during the Pandemic Covid-19 in Indonesia? - Hidayah, Yayuk; Halimah, Lili; Trihastuti, Meiwatizal; Dewie, Dinie Anggraeni; Feriandi, Yoga Ardian; Dianasari, Dianasari (IJERI: International Journal of Educational Research and Innovation, 2020)
Number of problems as cause of Covid-19 pandemic have continued to appear in various sectors as it rapidly spreads. In education sector, students are no longer able to study freely in classroom and even go to school to study. In this case, changing the way of learning is a form of consistency to educate them in various situations and conditions, especially during the Covid-19 pandemic. In this study, we investigated how the response of students through prospective elementary school teachers in Indonesia to learn Citizenship Education which was implemented remotely at home with an online learning scheme during the Covid-19 Pandemic. We used qualitative and quantitative research method in this study. To collect data, we used questionnaires distributed to 508 students in the Special Region of Yogyakarta, Bandung City, Cirebon City West Java Province by using Google Form. In addition, we also conducted some interviews with a number of students by using an online application to obtain valid data. Based on the research, there were good and bad student learning attitudes in the Citizenship Education course. A good student learning attitude was shown by enthusiasm in the learning-based video, while the bad attitude of students is shown by the lack of effectiveness in understanding the concept of Citizenship Education.